NON PHARMACOLOGICAL TREATMENTS FOR BREAST ENGORGEMENT: A SYSTEMATIC REVIEW - Ertitawai Siregar; Triana Sri Hardjanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background:. Mothers often suffer breast engorgement at the beginning of postpartum, and one of the causes is early breastfeeding cessation. Management of breast engorgement should be done well to support the success of exclusive breastfeeding. This study aimed to review and identify the non- pharmacological treatments that have potential effects on reduced breast engorgementMethods:This was a systematic review prepared according to the standard guidelines of the Joanna Briggs Institute (JBI). Article search used electronically. The two databases used were the PubMed and Cochrane library. English-language articles, and full text using the keywords of